3D ANIMATION DESIGN "SCIENCE, LANTERNS TO HEAVEN" USING THE POSE-TO-POSE METHOD - Desy Apriliyanti; Juniardi Nur Fadila; Fresy Nugroho (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2022)
In today's era, technology and communication have experienced very rapid development. Islamic values ​​raised through the media are an effort in people's lives today. Including through the media of 3D animated films that rely on entertaining audio-visuals and messages conveyed through animated films can also be easily captured by the audience. In addition, the selection of animated films is based on the number of animated films circulating on social media such as YouTube and other electronic media, and this film can affect the attention of many people. Animated film designed by the author with the theme of the importance of studying can lead to Allah SWT's heaven. Making this animated film will use Blender software version 2.80. The method used is "Pose-to-Pose" by determining each key pose movement to produce a good movement. Using this method makes the work more effective or faster; if there is an error in the pose, it can be easily corrected. The design of the 3D animated film entitled "Science, Lantern Towards Heaven" is expected to be useful for the audience and take the moral message in it, which is to increase enthusiasm for learning or studying